Women at work : an exploratory study on how Taiwanese females build guanxi and their attitudes toward Yingchou as a guanxi-building tool - Ang, Geraldine Shi Min (2010)
Guanxi is an important work resource in the Chinese culture. Yingchou in the form of he hua jiu is a crucial business practice, especially among men in Taiwan, for building guanxi; it is a gender-segregated activity such that the culture of yingchou is a barrier faced by Taiwanese females when building guanxi. This study explored the obstacles Taiwanese females faced when trying to build guanxi at work and looked at the alternative guanxi-building methods females engaged in; females’ attitudes toward yingchou as the key mean of building guanxi were also investigated. While females acknowledged the usefulness of yingchou as a guanxi-building tool, they did employ alternative methods of building guanxi through exchanges of ganqing. Implications of the results are discussed.